2006
DOI: 10.1108/09544780610685467
|View full text |Cite
|
Sign up to set email alerts
|

The development of an employee satisfaction model for higher education

Abstract: Purpose-Most studies on higher education focus on students as customers, and evaluate student levels of satisfaction/dissatisfaction with their programs, while generally neglecting teacher work satisfaction. Thus, this study evaluates how employee dissatisfaction with various investment items determines the improvement priority. Design/methodology/approach-This study used the academic literature to establish a satisfaction model for higher education employees. The model is divided into six dimensions: organisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
111
0
11

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(123 citation statements)
references
References 31 publications
1
111
0
11
Order By: Relevance
“…The employees that are not motivated for work have a very low business success. The unmotivated employees are not interested in the quality of the products and services; they do not identify with the organization's values, are not connected to the organization or their problems, the development or the success and are often ready to leave that organization (Balbaster Benavent et al, 2005, Chen &Yang, 2006Kondo, 1995;Francis & Young, 2012;Parker, 2003;Sethi, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The employees that are not motivated for work have a very low business success. The unmotivated employees are not interested in the quality of the products and services; they do not identify with the organization's values, are not connected to the organization or their problems, the development or the success and are often ready to leave that organization (Balbaster Benavent et al, 2005, Chen &Yang, 2006Kondo, 1995;Francis & Young, 2012;Parker, 2003;Sethi, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These dimensions are represented in the model below: Parasuraman, et al,1985:48 Despite its popularity, the SERVQUAL model has been criticised (for example, Cronin & Taylor, 1992;Teas, 1993a;Joseph & Joseph, 1997;O'Neill & Palmer, 2004;Chen et al, 2006). Because of such criticism of the SERVQUAL model, this research makes use of the modified SERVQUAL model (Parasuraman et al, 1991).…”
Section: Service Quality Models For Measuring Service Quality Improvementioning
confidence: 99%
“…Brysland and Curry (2001) and Jongbloed et al (2008) also note that knowledge of what satisfies stakeholders and a consideration of their role in society are important steps in quality improvement initiatives for HEIs in the delivery of service quality and the assessment of their relationships with different stakeholders. Chen, Yang, Shiau and Wang (2006) note that employee satisfaction in their current working environment leads to a greater willingness and efficiency in performing organisational activities. They continue by declaring that the degree of teacher satisfaction has an influence on the performance of the institutions.…”
Section: Importance Of Quality Improvement In Heismentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed in the results those assistant registrars are satisfied with the HRM practices and have a positive influence on job satisfaction. Chen et al, (2006) measured the job satisfaction of the 248 teachers in private university in China on the satisfaction determinants, namely organisation vision, respect, result feedback and motivation, management system, pay and benefits, and work environment. The analytical results showed that higher education employees focus on high salaries and fair promotion systems.…”
Section: Review Of Literaturementioning
confidence: 99%